2020
DOI: 10.17485/ijst/v13i25.828
|View full text |Cite
|
Sign up to set email alerts
|

Faculty members' readiness implementing e-learning in higher education Saudi Universities: A cross-sectional study

Abstract: Background/ Objectives: This article reports on an e-learning readiness study that was carried out to determine the institutional, individual, and communication factors of the two major stakeholder groups (teachers and institutions) in the higher education universities in Saudi Arabia. Methods: A sample of 139 faculty members working in ten higher education universities in Saudi Arabia was surveyed in this cross-sectional study. A pre-validated survey questionnaire of e-learning was adopted to collect data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…This observation could be attributed to the fact that the sampling population encompassed faculty members of academic institutions, and all of the participants were educated. Similar results were reported earlier by Tayyib et al (2020) while studying e-learning in Saudi Arabia. The differences with respect to the prior teaching experience in e-learning and using AI techniques impacted all the dimensions significantly, indicating that the entrants who had used these tools earlier had appreciated and embraced them.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation could be attributed to the fact that the sampling population encompassed faculty members of academic institutions, and all of the participants were educated. Similar results were reported earlier by Tayyib et al (2020) while studying e-learning in Saudi Arabia. The differences with respect to the prior teaching experience in e-learning and using AI techniques impacted all the dimensions significantly, indicating that the entrants who had used these tools earlier had appreciated and embraced them.…”
Section: Discussionsupporting
confidence: 91%
“…The differences with respect to the prior teaching experience in e-learning and using AI techniques impacted all the dimensions significantly, indicating that the entrants who had used these tools earlier had appreciated and embraced them. This kind of former experience would have also increased the educators' readiness to use these techniques (Tayyib et al, 2020). In accordance with our results, Alqahtani and Rajkhan (2020) explored the educators at Saudi universities to determine the factors associated with the e-learning adoption and found that the knowledge of the implementation strategies was a critical component of e-learning success in the COVID-19 crisis.…”
Section: Discussionsupporting
confidence: 79%
“…In this respect, current literature has investigated education institutions' readiness to online education in the following factors: technology, human resource, budget, and infrastructure (Azimi, 2013); computer self-efficacy, internet self-efficacy, online communication, self-directed learning, learner control and motivation towards e-learning (Yilmaz, 2017); technology, innovation, people, and selfdevelopment (Aydın & Tasci, 2005). According to Tayyib et al (2020) these dimensions could be more suitable when the organizations are at the beginning phase of the changes. On the other hand, Lokuge et al (2019) investigated the readiness to change under three main dimensions, which are change valance (support and commitment for change), change efficacy (resources and capabilities for required tasks), and contextual factors (organizational culture).…”
Section: Introductionmentioning
confidence: 99%
“…(31) . Hence, the e-learning of BBLMS simple, clear, and motivate the learners to use it effectively (32) .…”
Section: Discussionmentioning
confidence: 99%
“…As a result of Covid-19, education has changed dramatically and drastically, with the phenomenal rise of virtual learning, whereby teaching is held remotely. Research suggests that off-campus learning has been practiced to develop information retention and take less time, meaning the impact coronavirus has caused might be here to stay (3) . With this sudden transition away from the classroom in many https://www.indjst.org/ parts of the globe, few wonders whether online learning strategies will continue to persist post-pandemic and how such a change would alter the worldwide education market (4) .…”
Section: Introductionmentioning
confidence: 99%